Piano sonata no. 27 in E minor, op. 90, first edition reprinted by Breitkopf & Härtel - Beethoven, Ludwig van, 1770-1827 (composer):::Creator:::::::::::: (Germany; Breitkopf & Härtel; Leipzig, 2023)
Reprint of the first edition of the Piano Sonata in E minor, op. 90, originally published by Steiner, with plate number C.D.S.A.S. 2350 and price "20 gr." printed on title page.